The outlet design of flat fan nozzle varies the application time of day effect on nicosulfuron activity - Akbar Aliverdi; Abolfazl Aliverdi; Jason Connor Ferguson (Agraarteadus, 2021)

(untitled)
On two container-grown species, johnsongrass and velvetleaf, nicosulfuron was sprayed with the Anti-Drift Single, Dual, and Triplet Flat-Fan nozzles (AD/S, AD/D, AD/T nozzles, respectively) at 05:00 to 21:00, with a two-hour interval. At 5:00 to 11:00, nicosulfuron activity on both species was greatest with the AD/T followed by the AD/D and finally, the AD/S nozzle. At 15:00 to 19:00, however, nicosulfuron activity on johnsongrass was greatest with the AD/D, followed by the AD/T and finally, the AD/S nozzle, and nicosulfuron activity on velvetleaf was greatest with the AD/D followed by the AD/S and the AD/T nozzle had the lowest control. Nicosulfuron applied with the AD/T nozzle in the early morning caused the highest desiccation (70%) in both species. The best time to apply nicosulfuron was in the early morning. However, velvetleaf undergoes foliar nyctinasty depending on daylight, which made effective control achieved by only the AD/D and AD/T nozzles